2012
DOI: 10.1038/nature11094
|View full text |Cite
|
Sign up to set email alerts
|

Cis-regulatory control of corticospinal system development and evolution

Abstract: SummaryThe co-emergence of a six-layered cerebral neocortex and its corticospinal output system is one of the evolutionary hallmarks of mammals. However, the genetic programs that underlie their development and evolution remain poorly understood. Here we identify a conserved non-exonic element (E4) that acts as a cortex-specific enhancer for the nearby Fezf2, which is required for the specification of corticospinal neuron identity and connectivity. We find that SOX4 and SOX11 functionally compete with the repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 55 publications
4
169
0
Order By: Relevance
“…Therefore, the III-tubulin yet not give retinal progenitors the cue to start differentiating. Recently, Fezf2 and BDNF were found as targets of Sox11 in cortex and dorsal root ganglia, respectively (Salerno et al, 2012;Shim et al, 2012). Our microarray data of Sox11-KO retina showed rather elevated expression of Fezf2 and BDNF (data not shown), suggesting cell type-specific activation of genes by Sox11.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, the III-tubulin yet not give retinal progenitors the cue to start differentiating. Recently, Fezf2 and BDNF were found as targets of Sox11 in cortex and dorsal root ganglia, respectively (Salerno et al, 2012;Shim et al, 2012). Our microarray data of Sox11-KO retina showed rather elevated expression of Fezf2 and BDNF (data not shown), suggesting cell type-specific activation of genes by Sox11.…”
Section: Discussionmentioning
confidence: 84%
“…Members of the SoxC group, including Sox11 and Sox12, in addition to Sox4, might have essential function in early mouse embryonic organogenesis; they directly target the Tead2 gene, a crucial transcription factor in the Hippo signaling pathway (Bhattaram et al, 2010). Recent reports have also shown that Sox4 and Sox11 are necessary for the control of corticospinal system development; Sox4 and Sox11 directly regulate Fezf2, which encodes a key factor for the specification of identity and the connectivity of corticospinal neurons (Shim et al, 2012). In C2C12 myoblasts, our quantitative RT-PCR results showed that the levels of Sox11 and Sox12 transcripts were extremely low compared with the level of Sox4; their expression pattern did not change during myoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the phenotypic effects in hippocampus of inactivating these genes, we selectively inactivated Sox4 and Sox11 in neural progenitors of the cerebral cortex, including the hippocampus, by crossing floxed Sox4 and Sox11 mice with the Emx1-Cre transgenic line (Shim et al, 2012). Based on our network results and on previous findings from other labs (Mu et al, 2012), we would predict that knocking out these hub genes would significantly affect development of DG granule cells.…”
Section: −11mentioning
confidence: 99%